Modelling the effects of perceived credibility on consumers’ attitudes and purchase intention: empirical evidence from celebrity entrepreneur endorser advertisement / Mazzini Muda - Muda, Mazzini (Institute of Graduate Studies, UiTM, 2014)
The use of celebrities as endorser of product in advertisements is a very popular strategy in marketing communications. Empirical evidences from western samples justify the hiring of celebrities in advertisements. While the strategy has spread across other countries around the world, there is a lack of studies done to determine the effectiveness of this strategy in other markets especially the Asian markets. Moreover, a new phenomenon has emerged where celebrities become entrepreneurs by starting ventures and endorsing their own brand in advertisement. As the strategy becomes more prevalent across many media, there is a need to assess the value added by celebrities in advertisements. In this regard, the credibility of the celebrity as the source in the communication process becomes the primary focus of this study.